The effect of Islamic attributes to consumer satisfaction: a meta-analysis - Sumardi, Retno Santi; Mahomed, Anuar Shah Bali; Ab Aziz, Yuhanis
In the growing halal industry, there are differences of opinion among researchers about the effect of Islamic attributes on consumer satisfaction. Therefore, this paper aims to evaluate the effect of Islamic attributes on consumer satisfaction. The Prisma flow diagram indicated 23 papers and consists of 59 studies to analyze with JASP Software. The study identifies significant authors, dominant publishers, methodology, and theories commonly employed in this topic. The result proves that catering to Muslim needs through Islamic attributes can significantly enhance consumer satisfaction and th e presence of other variables as moderators will strengthen tourist satisfaction.